The Membrane Sensors Sensitive to Fluoxetine - Optimization of the Analytical Parameters - Joanna Drozd, (Journal of Basic & Applied Sciences, 2015)
Background: The analytical characteristics of electrodes containing liquid PVC membrane depend on the purity of the electroactive material and the applied membrane solvents. Methods: Fluoxetine - one H-bond donor, formed ion-associated complexes with tetraphenylborate, tetrakis(4-chlorophenyl)borate and dipicrylamine. To confirm the quality and purity obtained complexes the elemental and TLC analysis were performed. The construction and general characteristics of fluoxetine ion-selective plastic membrane sensors, based on the use of a fluoxetine – tetrakis(4-chlorophenyl)borate ion-pair complex as electroactive material with 2-nitrophenyloctyl ether, bis(2-ethylhexyl)sebacate, bis(2-butylpentyl)adipate and 1-isopropyl-4-nitrobenzene as solvent mediators. Results: The electrode containing Fl-ClTPB-NPhOE (fluoxetine-tetrakis(4-chlorophenyl)borate-2-nitrophenyloctyl ether showed a linear response to fluoxetine at concentration ranges of 30.93 – 2.16 g·L-1 with a super Nernstian cationic slope 60.19 mV·decade-1. Conclusions: This Fl-ClTPB-NPhOE sensor was used for the potentiometric determination of the content of fluoxetine hydrochloride in pure form and pharmaceutical formula.